On the issue of choosing vertical and horizontal connections in a bogie for freight cars of high-speed trains - G. I. Gadzhimetov; G. I. Petrov; Yu. A. Panin; I. E. Il’in (Вестник Научно-исследовательского института железнодорожного транспорта)
To increase the competitive advantages of rail freight transportation, the long-term development program of the Russian Railways provides for an increase in the speed of freight trains. The design speed of freight cars currently operating on the railway network is mainly 120 km/h, and the permitted speed is limited to 90 km/h. One of the possible solutions to the problem is the introduction of freight cars with an increased speed. At JSC “VNIIZHT” and JSC “VNIKTI”, work is being carried out on the selection of structures, the development of safety requirements, theoretical and experimental studies of freight traffic at increased speeds. In 2017—2018 at the Belorechenskaya—Maikop high-speed test range of the North Caucasian Railway, specialists of JSC “VNIIZHT” carried out running tests of a prototype of a platform car for transporting containers with a design speed of 160 km/h, developed by JSC “VNIKTI”. In the design of the platform car, a bogie is used, which is an analogue of the bogie of trailed cars of electric trains ED4 and ED9, with the selection of the stiffness of the springs in the spring suspension steps to comply with the difference in the level of the automatic coupler from the rail head in the “container” and “gross” modes. Analysis of the results of running tests allows determining the ways to improve the design of the bogie. To select design solutions for the purpose of ensuring safety, a review of the studies of domestic scientists aimed at studying the dynamic properties of railway rolling stock with various designs of the carriage part was carried out. Tests were carried out on prototypes of rolling stock having different elastic-dissipative connections in the “body-bogie-wheelsets” system. Based on the results of the analysis, design solutions have been determined that allow achieving satisfactory dynamic qualities for a freight car at a speed of up to 140 km/h. The adopted design solutions were tested on the basis of the results of theoretical studies of the dynamic properties of a platform car with a new bogie, carried out by the method of computer simulation. Increasing the flexibility of the spring suspension and the horizontal connection of the body with the bogie made it possible to improve the dynamic qualities of freight cars. To assess the safety during certification, it is required to develop a standard that would take into account the design features of car bogies, designed for increased speed.